Ni3ZnC0.7-atNiZn catalyst as well as preparation method and application thereof

By preparing the Ni3ZnC0.7@NiZn catalyst, the problem of insufficient selectivity and stability in the electrocatalytic carbon dioxide reduction reaction was solved, and efficient conversion of carbon dioxide into carbon monoxide was achieved, which inhibited the competitive hydrogen evolution reaction and improved the structural stability and performance of the catalyst.

CN120485842APending Publication Date: 2025-08-15EAST CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510639557.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

In the existing electrocatalytic carbon dioxide reduction reaction (CO2RR), the selectivity and stability of the catalyst are insufficient, and the synthesis of traditional diatomic catalysts is complex and energy consumption is high, resulting in uneven catalytic performance and reduced active sites.

Method used

The NiZn diatom pair and nitrogen-doped carbon nanotube structure were synthesized by hydrothermal reaction, stirring, standstill and carbonization steps to form a stable NiZn diatom catalyst for electrocatalyzing carbon dioxide reduction.

Benefits of technology

The selectivity of carbon dioxide reduction to carbon monoxide is improved, competitive hydrogen evolution reaction is inhibited, the structural stability and catalytic performance of the material are enhanced, and efficient electrocatalytic carbon dioxide conversion is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120485842A_ABST
    Figure CN120485842A_ABST
Patent Text Reader

Abstract

The invention provides a Ni3ZnC0.7 atNiZn catalyst as well as a preparation method and application thereof. The preparation method of the Ni3ZnC0.7 atNiZn catalyst comprises the following steps: step 1), mixing and dissolving nickel nitrate and ethylene glycol according to a certain proportion, and then carrying out hydrothermal reaction to obtain colloid; 2) adding a certain volume of colloid into a methanol solution containing zinc nitrate, and stirring to obtain a mixed liquid; 3) adding a methanol solution containing 2-methylimidazole into the mixed liquid, stirring, standing at room temperature to obtain a NiOx ZIF-8 composite structure product, washing, drying, and collecting to obtain NiOx ZIF-8 composite structure powder; and 4) heating and carbonizing the NiOx-coated ZIF-8 composite structure powder in inert gas to obtain the Ni3ZnC0.7-coated NiZn catalyst, and the prepared Ni3ZnC0.7-coated NiZn catalyst is suitable for being used as an electrocatalytic carbon dioxide electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Ni3ZnC 0.7 @NiZn catalyst and its preparation method and application belong to the field of electrochemical reduction catalyst. Background Art

[0002] Due to global warming and the energy crisis, carbon dioxide (CO2) emissions have become an increasingly pressing issue, and there is an urgent need to accelerate technological innovation and breakthroughs in CO2 utilization. The electrocatalytic carbon dioxide reduction reaction (CO2RR) can convert CO2 into valuable chemicals or fuels and is a key strategy to reduce CO2 emissions and achieve efficient resource utilization. However, due to the high C=O bond energy in the CO2 molecule, the slow multi-step proton-coupled electron transfer kinetics of CO2 activation and intermediate formation, and the inevitable competitive hydrogen evolution reaction (HER), the selectivity and stability of CO2RR remain unsatisfactory. The development of efficient electrocatalysts with high selectivity and stability is crucial for practical applications.

[0003] Single-atom catalysts (SACs) have attracted extensive research and rapid development due to their high atomic utilization, strong metal-support interactions, and the ability to regulate the coordination environment. However, the synthesis of SACs usually requires precise control and involves complex synthesis techniques, which increases cost and technical difficulty. In addition, due to the high surface energy of metal atoms, they easily migrate or aggregate into metal particles, resulting in a reduction in active sites, which negatively affects catalytic performance and long-term stability. At the same time, SACs are prone to electronic structure changes during the catalytic process, which makes it challenging to regulate their electronic properties to optimize catalytic performance.

[0004] Compared with SACs, diatomic catalysts (DACs) composed of two coupled heteronuclear metal atomic sites show obvious advantages in coordination environment, quantum size effect and interaction with charge carriers. Diatomic catalysts have a unique structure, which enhances stability through the strong interaction between the two metal atoms and reduces the possibility of atomic migration or aggregation; in addition, the dual active sites produce a synergistic effect, which can optimize the reaction pathway and improve the overall catalytic efficiency; however, the traditional DACs preparation process usually requires high-temperature calcination of more than 1000°C, which consumes a lot of energy, and the prepared raw materials produce toxic gases during the pyrolysis process, which limits their practical application; in addition, due to the lack of precise synthesis methods, the catalyst structure is still uncontrollable, resulting in large differences in the electrocatalytic performance of different batches; therefore, there is an urgent need for a reliable method to accurately synthesize bimetallic pairs to achieve a uniform catalyst structure and facilitate the practical application of diatomic catalysts. Summary of the Invention

[0005] The present invention proposes a Ni3ZnC 0.7 @NiZn catalyst and its preparation method and application, the purpose of which is to synthesize a diatomic catalyst with high selectivity for the electrocatalytic reduction of carbon dioxide to carbon monoxide.

[0006] The technical solution of the present invention: a Ni3ZnC 0.7 @NiZn catalyst, whose structure includes NiZn diatomic pairs, Ni3ZnC 0.7 Nanoparticles, nitrogen-doped carbon nanotubes; among them, Ni3ZnC 0.7 The nanoparticles are located at one end of the nitrogen-doped carbon nanotubes, and the NiZn diatomic pairs are dispersed on the surface of the nitrogen-doped carbon nanotubes.

[0007] A Ni3ZnC 0.7 A method for preparing a NiZn catalyst, the method comprising: Step 1), nickel nitrate and ethylene glycol are mixed and dissolved in a certain proportion and then subjected to a hydrothermal reaction to obtain a colloid; Step 2), adding a certain volume of colloid into a methanol solution containing zinc nitrate and stirring to obtain a mixed liquid; Step 3) Add methanol solution containing 2-methylimidazole to the mixed liquid obtained in step 2) and stir, then let it stand at room temperature to obtain NiO x @ZIF-8 composite structure product; NiO x The @ZIF-8 composite structure product was washed and dried, and NiO was collected. x @ZIF-8 composite structure powder; Step 4), NiO obtained in step 3) x @ZIF-8 composite structure powder is heated and carbonized in an inert gas, and Ni3ZnC is collected. 0.7 @NiZn catalyst.

[0008] Furthermore, in step 1), the mass volume ratio of nickel nitrate to ethylene glycol is 1 g: (10-30) mL; the hydrothermal reaction in step 1) is carried out at 100° C. to 180° C. for 2 to 6 hours; and the stirring time in step 2) is 0.5 to 2 hours.

[0009] Furthermore, the concentration of zinc nitrate in the methanol solution containing zinc nitrate in step 2) is 0.05 mol / L to 0.1 mol / L; and the volume ratio of the colloid to the methanol solution containing zinc nitrate in step 2) is 1:(10-20).

[0010] Furthermore, the concentration of 2-methylimidazole in the methanol solution containing 2-methylimidazole in step 3) is 0.1 mol / L to 0.5 mol / L; and the volume ratio of the mixed liquid to the methanol solution containing 2-methylimidazole in step 3) is 1:(0.5-2).

[0011] Furthermore, the stirring time in step 3) is 1 to 3 hours; and the standing time at room temperature in step 3) is 1 to 6 hours.

[0012] Furthermore, in step 4), NiO x The ZIF-8 composite structure powder is first heated to 300°C in an inert gas and maintained for 1 hour, and then heated to 750°C to 850°C for heating and carbonization. The heating time is 1 to 4 hours.

[0013] A method using Ni3ZnC 0.7 A method for preparing an electrocatalytic carbon dioxide reduction electrode using a NiZn catalyst, the method comprising: Step (1), Ni3ZnC 0.7 @NiZn catalyst, dispersion liquid and binder are mixed in a certain ratio and ultrasonically dispersed to form a solution; Step (2): evenly apply the solution formed in step (1) on the hydrophobic carbon paper and air dry it to obtain the diatomic catalyst Ni3ZnC 0.7 @NiZn electrode.

[0014] Furthermore, the dispersion liquid is any one of deionized water, anhydrous ethanol, and isopropyl alcohol, or a combination of several thereof; and the binder is any one of polyacrylic acid, perfluorinated resin, and fluorinated ethylene propylene copolymer, or a combination of several thereof.

[0015] Furthermore, the Ni3ZnC 0.7 @The mass volume ratio of NiZn catalyst, dispersion liquid and binder is 1 mg: (50-100) ml: (1-10) ml.

[0016] Beneficial effects of the present invention: 1) Ni3ZnC of the present invention 0.7 @NiZn catalyst preparation method is flexible, simple to operate, the raw materials are non-toxic, and the product structure is adjustable; 2) Ni3ZnC prepared by the method of the present invention 0.7 NiZn catalyst is a highly efficient catalytic material, and its abundant specific surface area is conducive to gas mass transfer and ion transport; 3) Ni3ZnC prepared by the present invention 0.7The NiZn catalyst enhances the adsorption and desorption of intermediates during the CO2 electrocatalytic process through the synergistic effect between the two NiZn atoms, significantly improving the selectivity of carbon dioxide reduction to carbon monoxide while effectively inhibiting the competitive hydrogen evolution reaction. 4) The regulation of the carbonization temperature during the preparation process of the present invention optimizes the material structure and enhances the structural stability of the material; 5) Using Ni3ZnC prepared by the present invention 0.7 The electrocatalytic carbon dioxide electrode prepared with @NiZn catalyst is applied to the electrocatalytic carbon dioxide reduction device, which can improve the selectivity of carbon dioxide reduction to carbon monoxide, while effectively inhibiting the competitive hydrogen evolution reaction. The electrode material prepared by this invention can realize the conversion of carbon dioxide into high-value carbon monoxide by electrocatalysis, which is of great significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Attachment Figure 1 It is Ni3ZnC in Example 1 of the present invention 0.7 @SEM image of NiZn material.

[0018] Attachment Figure 2 It is Ni3ZnC in Example 1 of the present invention 0.7 @Energy dispersion diagram of NiZn material.

[0019] Attachment Figure 3 It is Ni3ZnC in Example 1 of the present invention 0.7 @TEM image of NiZn material.

[0020] Attachment Figure 4 It is Ni3ZnC in Example 1 of the present invention 0.7 @Spherical aberration electron microscope image of NiZn material.

[0021] Attachment Figure 5 It is Ni3ZnC in Example 2 of the present invention 0.7 SEM image of .

[0022] Attachment Figure 6 This is a SEM image of Ni in Example 3 of the present invention.

[0023] Attachment Figure 7 It is Ni3ZnC in Example 1 of the present invention 0.7 @XRD pattern of NiZn material.

[0024] Attachment Figure 8 It is Ni3ZnC in Example 1 of the present invention 0.7 High-resolution transmission electron microscopy image of @NiZn material.

[0025] Attachment Figure 9It is Ni3ZnC in Example 1 of the present invention 0.7 @Raman spectrum of NiZn material.

[0026] Attachment Figure 10 It is Ni3ZnC in Example 1 of the present invention 0.7 @NiZn material electrocatalytic CO2 reduction performance test diagram.

[0027] Attachment Figure 11 This is a test diagram of the electrocatalytic CO2 reduction performance in Examples 1, 2, and 3 of the present invention.

[0028] Attachment Figure 12 It is Ni3ZnC in Example 1 of the present invention 0.7 @Faraday efficiency diagram of NiZn material electrocatalytic CO2 reduction.

[0029] Attachment Figure 13 This is a Faraday efficiency diagram of electrocatalytic CO2 reduction in Example 2 of the present invention.

[0030] Attachment Figure 14 This is a Faraday efficiency diagram of electrocatalytic CO2 reduction in Example 3 of the present invention.

[0031] Attachment Figure 15 It is Ni3ZnC in Example 1 of the present invention 0.7 @NiZn material electrocatalytic CO2 reduction stability test diagram. DETAILED DESCRIPTION

[0032] A Ni3ZnC 0.7 @NiZn catalyst, whose structure includes NiZn diatomic pairs, Ni3ZnC 0.7 Nanoparticles, nitrogen-doped carbon nanotubes (NCNT); among them, Ni3ZnC 0.7 The nanoparticles are located at one end of the nitrogen-doped carbon nanotubes, and the NiZn diatomic pairs are dispersed on the surface of the nitrogen-doped carbon nanotubes.

[0033] A Ni3ZnC 0.7 A method for preparing a NiZn catalyst, the method comprising: Step 1), nickel nitrate and ethylene glycol are mixed and dissolved in a certain proportion and then subjected to a hydrothermal reaction to obtain a colloid; Step 2), adding a certain volume of colloid into a methanol solution containing zinc nitrate and stirring to obtain a mixed liquid; Step 3) Add a methanol solution containing 2-methylimidazole (C4H6N2) to the mixed liquid obtained in step 2) and stir, then let it stand at room temperature to obtain NiO x @ZIF-8 composite structure product; NiO x The @ZIF-8 composite structure product was washed and dried, and NiO was collected.x @ZIF-8 composite structure powder; Step 4), NiO obtained in step 3) x @ZIF-8 composite structure powder is heated and carbonized in an inert gas, and Ni3ZnC is collected. 0.7 @NiZn catalyst; prepared Ni3ZnC 0.7 @NiZn catalyst is a diatomic catalyst.

[0034] The mass volume ratio g / mL of nickel nitrate to ethylene glycol in step 1) is preferably 1 g: (10-30) mL, that is, 1 g of nickel nitrate is mixed and dissolved with every 10 mL to 30 mL of ethylene glycol, and then a hydrothermal reaction is carried out; the mass volume ratio g / mL of nickel nitrate to ethylene glycol in step 1) is further preferably 1 g: 30 mL.

[0035] The hydrothermal reaction in step 1) is preferably carried out at 100° C. to 180° C. for 2 to 6 hours to obtain the colloid; the hydrothermal reaction in step 1) is further preferably carried out at 180° C. for 2 hours.

[0036] The concentration of zinc nitrate in the methanol solution containing zinc nitrate in step 2) is preferably 0.05 mol / L to 0.1 mol / L; the concentration of zinc nitrate in the methanol solution containing zinc nitrate in step 2) is further preferably 0.06 mol / L.

[0037] The volume ratio of the colloid to the methanol solution containing zinc nitrate in step 2) is preferably 1:(10-20); the volume ratio of the colloid to the methanol solution containing zinc nitrate in step 2) is more preferably 1:16.5.

[0038] The stirring time in step 2) is preferably 0.5 to 2 hours; the stirring time in step 2) is more preferably 1 hour.

[0039] The concentration of 2-methylimidazole in the methanol solution containing 2-methylimidazole in step 3) is preferably 0.1 mol / L to 0.5 mol / L; the concentration of 2-methylimidazole in the methanol solution containing 2-methylimidazole in step 3) is more preferably 0.5 mol / L.

[0040] The volume ratio of the mixed liquid to the methanol solution containing 2-methylimidazole in step 3) is preferably 1:(0.5-2); the volume ratio of the mixed liquid to the methanol solution containing 2-methylimidazole in step 3) is more preferably 1:1.

[0041] The stirring time in step 3) is preferably 1 to 3 hours; the stirring time in step 3) is more preferably 3 hours.

[0042] The standing time at room temperature in step 3) is preferably 1 to 6 hours; the standing time at room temperature in step 3) is more preferably 5 hours.

[0043] In step 4), NiO x The ZIF-8 composite structure powder is first heated to 300°C in an inert gas and maintained for 1 hour, and then preferably heated to 750°C to 850°C for heating and carbonization, and the heating time is 1 to 4 hours; in step 4), NiO x The ZIF-8 composite structure powder is further preferably heated and carbonized at 800° C. in an inert gas for 4 hours.

[0044] Ni3ZnC prepared by the present invention 0.7 @NiZn catalyst includes NiZn diatomic pairs, Ni3ZnC 0.7 Nanoparticles, nitrogen-doped carbon nanotubes; NiZn diatomic pair sites are dispersed on the surface of nitrogen-doped carbon nanotubes.

[0045] The present invention is to react nickel nitrate with ethylene glycol under the hydrothermal reaction conditions of 100°C to 180°C for 2 hours to 6 hours. 2+ Under the action of ethylene glycol, it is partially hydrolyzed or reduced to form highly dispersed nickel oxide nanoparticle colloid (NiO colloid), which is green in color. The NiO colloid produced by the preparation process of the present invention is added to a methanol solution containing zinc nitrate and reacts with 2-methylimidazole to form a light green NiO x @ZIF-8 composite structure; NiO x During the carbonization process of ZIF-8 powder at 750℃~850℃, NiO x The decomposition of the ZIF-8 structure provides abundant carbon and nitrogen sources, forming a nitrogen-doped carbon nanotube skeleton with abundant defects. Most of the zinc atoms evaporate at high temperatures, but a small amount of Zn atoms remain and diffuse during the carbonization process, interacting with Ni after high-temperature reduction of NiO, and forming a part of the alloy Ni3ZnC 0.7 Nanoparticles, another part of isolated Ni atoms and Zn atoms are anchored in the nitrogen-doped sites in the form of pairs, forming a stable NiZn diatomic structure.

[0046] The present invention uses a metal framework derivation method to synthesize a diatomic catalyst with high selectivity for electrocatalytic reduction of carbon dioxide to carbon monoxide; the prepared Ni3ZnC 0.7 @NiZn catalyst is suitable for electrode active materials, especially for electrocatalytic carbon dioxide electrode active materials.

[0047] A method of using prepared Ni3ZnC 0.7A method for preparing an electrocatalytic carbon dioxide reduction electrode using a NiZn catalyst, the method comprising: Step (1), Ni3ZnC 0.7 @NiZn catalyst, dispersion liquid and binder are mixed in a certain ratio and ultrasonically dispersed to form a solution; Step (2): evenly apply the solution formed in step (1) on the hydrophobic carbon paper and air dry it to obtain the diatomic catalyst Ni3ZnC 0.7 @NiZn electrode.

[0048] Using the prepared Ni3ZnC 0.7 In the method for preparing an electrocatalytic carbon dioxide reduction electrode using @NiZn catalyst, the dispersion liquid in step (1) is preferably any one or a combination of deionized water, anhydrous ethanol, and isopropanol; the dispersion liquid in step (1) is further preferably anhydrous ethanol.

[0049] The binder in step (1) is preferably any one of polyacrylic acid (PAA), perfluorinated resin (Nafion), and fluorinated ethylene propylene copolymer (FEP), or a combination thereof; the binder in step 1) is further preferably perfluorinated resin (Nafion).

[0050] Preferably, in step (1), Ni3ZnC 0.7 The mass volume ratio (mg / ml / ml) of @NiZn catalyst, dispersion liquid, and binder is preferably 1 mg: (50-100) ml: (1-10) ml, more preferably 1 mg: 100 ml: 5 ml.

[0051] The present invention will be further described below with reference to specific embodiments. Example 1

[0052] A Ni3ZnC 0.7 A method for preparing a NiZn catalyst, the method comprising the following steps: Nickel nitrate and ethylene glycol were mixed and dissolved in a mass volume ratio of 1g:30ml and then placed in a sealed polytetrafluoroethylene reactor and maintained at 180℃ for 2 hours to obtain green nickel oxide nanoparticle colloid (NiO colloid). The nickel oxide nanoparticle colloid was added to a methanol solution with a zinc nitrate concentration of 0.06 mol / L and stirred for 1 hour to obtain a mixed liquid. The volume ratio of the nickel oxide nanoparticle colloid to the methanol solution containing zinc nitrate was 1:16.5. A methanol solution containing 0.5 mol / L 2-methylimidazole was added to the obtained mixed liquid and stirred for 3 hours. The volume ratio of the mixed liquid to the methanol solution containing 0.5 mol / L 2-methylimidazole was 1:1. The mixture was then allowed to stand at room temperature for 5 hours to obtain light green NiO. x@ZIF-8 composite structure product, the light green NiO x The @ZIF-8 composite structure product was washed and dried, and the light green NiO was collected. x @ZIF-8 composite structure powder, the light green NiO x The ZIF-8 composite powder was first heated to 300°C in an inert atmosphere and maintained for 1 hour, then heated to 800°C for 4 hours, and then cooled to room temperature. The resulting catalyst was labeled Ni3ZnC 0.7 @NiZn.

[0053] In this Example 1, under the hydrothermal reaction conditions of 180°C for 2 hours, nickel nitrate reacts with ethylene glycol to generate a green colloid, which is mainly due to the fact that Ni 2+ Under the action of ethylene glycol, it is partially hydrolyzed or reduced to form highly dispersed nickel oxide nanoparticle colloid, which is green in color. In the preparation process of Example 1, NiO colloid is added to a methanol solution containing zinc nitrate and reacts with 2-methylimidazole to form light green NiO. x @ZIF-8 composite structure; In this embodiment, during the carbonization process at 800℃, NiO x The decomposition of the ZIF-8 structure provides abundant carbon and nitrogen sources, forming a nitrogen-doped carbon nanotube skeleton with abundant defects. Most of the zinc atoms evaporate at high temperatures, but a small amount of Zn atoms remain and diffuse during the carbonization process, interacting with Ni after high-temperature reduction of NiO, and forming a part of the alloy Ni3ZnC 0.7 Nanoparticles, another part of isolated Ni atoms and Zn atoms are anchored in the nitrogen-doped sites in the form of pairs, forming a stable NiZn diatomic structure.

[0054] The Ni3ZnC prepared in Example 1 was observed using a scanning electron microscope. 0.7 @Surface morphology of NiZn catalyst, SEM photo attached Figure 1 It shows that the catalyst has a typical carbon nanotube morphology; Figure 2 Ni3ZnC prepared in Example 1 0.7 @The energy dispersion spectrum of NiZn catalyst proves the formation of nitrogen-doped carbon nanotubes; Figure 3 Ni3ZnC prepared in Example 1 0.7 TEM image of @NiZn catalyst, the image clearly shows that the catalyst has carbon nanotube morphology, and Ni3ZnC 0.7 Nanoparticles are located on the top of nitrogen-doped carbon nanotubes, Ni3ZnC 0.7 Nanoparticles act as catalytic cores during the growth of carbon tubes, inducing the directional epitaxy of carbon tubes. Figure 4The NiZn diatomic pairs are marked with circles, indicating the presence of diatomic pairs in the material. The Ni3ZnC prepared in this example 0.7 @NiZn catalyst includes NiZn diatomic pairs, Ni3ZnC 0.7 Nanoparticles, nitrogen-doped carbon nanotubes; NiZn diatomic pairs are dispersed on the surface of nitrogen-doped carbon nanotubes; Figure 7 Ni3ZnC prepared in Example 1 0.7 The XRD spectrum of @NiZn catalyst, in which the diffraction peaks at 42.8°, 49.8° and 73° correspond to Ni3ZnC 0.7 The (111), (200) and (220) crystal planes of Ni3ZnC 0.7 @NiZn catalyst has a graphitized structure; Figure 8 Ni3ZnC prepared in Example 1 0.7 High-resolution transmission electron microscopy of NiZn catalyst, Ni3ZnC 0.7 The nanoparticles are encapsulated in carbon nanotubes, and the carbon shell lattice spacing is about 0.33 nm, corresponding to the (002) plane of graphite carbon; Figure 9 shows the Ni3ZnC prepared in Example 1. 0.7 Raman spectrum of @NiZn catalyst, 1350 cm -1 (D band) and 1580 cm -1 (G band) peak intensity ratio (I D / I G ) is 2.13, reflecting that the catalyst has a high degree of carbon structural defects, which mainly originate from nitrogen-doped carbon nanotubes. During the growth process, the doping of nitrogen elements further breaks the order of the carbon skeleton and introduces more defect sites, resulting in a significant enhancement of the D peak; the high degree of carbon structural defects is expected to improve the electron transfer efficiency, thereby promoting the electrocatalytic carbon dioxide reduction. Example 2

[0055] A Ni3ZnC 0.7 A method for preparing a catalyst, the method comprising the following steps: Nickel nitrate and ethylene glycol were mixed and dissolved in a mass volume ratio of 1g:30ml and then placed in a sealed polytetrafluoroethylene reactor and maintained at 180℃ for 2 hours to obtain green nickel oxide nanoparticle colloid (NiO colloid). The nickel oxide nanoparticle colloid was added to a methanol solution with a zinc nitrate concentration of 0.06 mol / L and stirred for 1 hour to obtain a mixed liquid. The volume ratio of the nickel oxide nanoparticle colloid to the methanol solution containing zinc nitrate was 1:16.5. A methanol solution containing 0.5 mol / L 2-methylimidazole was added to the obtained mixed liquid and stirred for 3 hours. The volume ratio of the mixed liquid to the methanol solution containing 0.5 mol / L 2-methylimidazole was 1:1. The mixture was then allowed to stand at room temperature for 5 hours to obtain light green NiO. x @ZIF-8 composite structure product, the light green NiO x The @ZIF-8 composite structure product was washed and dried, and the light green NiO was collected. x @ZIF-8 composite structure powder, the light green NiO x The ZIF-8 composite powder was first heated to 300°C in an inert gas atmosphere for 1 hour, then heated to 700°C for 4 hours, and then cooled to room temperature to obtain Ni3ZnC 0.7 Catalyst; if attached Figure 5 As shown, heating at 700°C for 4 hours does not result in the formation of carbon nanotube morphology. Example 3

[0056] A method for preparing a Ni catalyst, the method comprising the following steps: Nickel nitrate and ethylene glycol were mixed and dissolved in a mass volume ratio of 1g:30ml and then placed in a sealed polytetrafluoroethylene reactor and maintained at 180℃ for 2 hours to obtain green nickel oxide nanoparticle colloid (NiO colloid). The nickel oxide nanoparticle colloid was added to a methanol solution with a zinc nitrate concentration of 0.06 mol / L and stirred for 1 hour to obtain a mixed liquid. The volume ratio of the nickel oxide nanoparticle colloid to the methanol solution containing zinc nitrate was 1:16.5. A methanol solution containing 0.5 mol / L 2-methylimidazole was added to the obtained mixed liquid and stirred for 3 hours. The volume ratio of the mixed liquid to the methanol solution containing 0.5 mol / L 2-methylimidazole was 1:1. The mixture was then allowed to stand at room temperature for 5 hours to obtain light green NiO. x @ZIF-8 composite structure product, the light green NiO x The @ZIF-8 composite structure product was washed and dried, and the light green NiO was collected. x @ZIF-8 composite structure powder, the light green NiO xThe ZIF-8 composite structure powder was first heated to 300℃ in an inert gas and maintained for 1 hour, then heated to 900℃ for 4 hours, cooled to room temperature and collected to obtain the Ni catalyst; the ZIF-8 composite structure powder was heated to 300℃ in an inert gas and maintained for 1 hour, then heated to 900℃ for 4 hours, and the Zn atoms were volatilized to a high degree. Figure 6 As shown in the figure, the catalyst structure collapsed and exhibited an irregular flake morphology. Example 4

[0057] Using Ni3ZnC prepared in Example 1 0.7 A method for preparing an electrocatalytic carbon dioxide electrode using a NiZn catalyst, the method comprising: Ni3ZnC 0.7 @NiZn catalyst, anhydrous ethanol, and perfluorinated resin (Nafion) were dissolved in a ratio of 1:100:5 (mg / ml / ml), ultrasonically dispersed, and evenly drop-coated on hydrophobic carbon paper. The mixture was then air-dried to obtain an electrocatalytic carbon dioxide electrode. Example 5

[0058] The electrocatalytic carbon dioxide electrode obtained in Example 4 is used in an electrolytic device for electrocatalytic carbon dioxide reduction, which includes: assembling an electrolytic device with the electrocatalytic carbon dioxide electrode prepared in Example 4 as a cathode, a platinum mesh electrode as an anode, and a proton exchange membrane as a diaphragm, and using a potassium bicarbonate (KHCO3) solution with a concentration of 0.5 mmol / L as an electrolyte solution. In order to further verify the specificity and selectivity of the catalyst of the present invention for the CO2 reduction reaction, carbon dioxide and argon gas are separately introduced into the cathode end, and a certain voltage is applied to the cathode for electrocatalytic carbon dioxide reduction; the gaseous product generated by the reduction is introduced into a gas chromatograph for online analysis; since argon is an inert gas and does not participate in any electrochemical reduction reaction under experimental conditions, the current contribution under argon conditions comes from the hydrogen evolution reaction. Under a CO2 atmosphere, the Ni3ZnC prepared by the present invention 0.7 @NiZn catalyst showed significant current response at a lower overpotential, but only showed a weak current under argon atmosphere, indicating that the Ni3ZnC prepared by the present invention 0.7 @NiZn catalyst has good CO2 catalytic activity.

[0059] As attached Figure 10 As shown in the figure, linear voltammetry scans were performed in argon and carbon dioxide atmospheres, respectively. The two showed different overpotentials, among which the overpotential in carbon dioxide atmosphere was smaller, as shown in the attached figure. Figure 11 Compared with the electrocatalytic carbon dioxide electrode prepared by the method of Example 4 using the catalysts prepared in Examples 2 and 3, the Ni3ZnC 0.7@NiZn catalyst shows the smallest overpotential in carbon dioxide atmosphere, which is more conducive to the electrocatalytic carbon dioxide; Figure 12 Shown is the Ni3ZnC prepared in Example 1 0.7 The NiZn catalyst exhibited excellent electrocatalytic performance in a wide temperature range, with the highest carbon monoxide Faraday efficiency reaching 97.3%. Figure 13 , Attachment Figure 14 The Faraday efficiency of the catalysts prepared in Example 2 and Example 3 for electrocatalysis of carbon dioxide to carbon monoxide is lower than that of the diatomic catalyst Ni3ZnC prepared in the present invention. 0.7 @NiZn is high, and the hydrogen evolution side reaction in Examples 2 and 3 is serious. Example 6

[0060] This embodiment provides a method of using the Ni3ZnC prepared in Example 1 in Example 4. 0.7 The electrocatalytic carbon dioxide electrode obtained using the @NiZn catalyst is used in an electrocatalytic device for carbon dioxide reduction. The single-pass operation steps are the same as those in Example 5, except that a long-term electrocatalytic test is performed at a constant voltage to verify the cyclic stability of the electrocatalytic carbon dioxide electrode during the electrocatalytic carbon dioxide reduction process.

[0061] From the attached Figure 15 As can be seen from the figure, the Faraday efficiency of the electrocatalytic carbon dioxide to carbon monoxide is maintained at above 97% in the 20-hour stability test. The catalyst shows excellent cycle stability. 0.7 The electrocatalytic carbon dioxide prepared by @NiZn has good performance and can efficiently convert carbon dioxide into carbon monoxide.

Claims

1. A Ni3ZnC 0.7 @NiZn catalyst, which is characterized by Including NiZn diatomic pairs, Ni3ZnC 0.7 Nanoparticles, nitrogen-doped carbon nanotubes; among them, Ni3ZnC 0.7 The nanoparticles are located at one end of the nitrogen-doped carbon nanotubes, and the NiZn diatomic pairs are dispersed on the surface of the nitrogen-doped carbon nanotubes.

2. A Ni3ZnC 0.7 @The preparation method of NiZn catalyst is characterized by include: Step 1), nickel nitrate and ethylene glycol are mixed and dissolved in a certain proportion and then subjected to a hydrothermal reaction to obtain a colloid; Step 2), adding a certain volume of colloid into a methanol solution containing zinc nitrate and stirring to obtain a mixed liquid; Step 3) Add methanol solution containing 2-methylimidazole to the mixed liquid obtained in step 2) and stir, then let it stand at room temperature to obtain NiO x @ZIF-8 composite structure product; NiO x The @ZIF-8 composite structure product was washed and dried, and NiO was collected. x @ZIF-8 composite structure powder; Step 4), NiO obtained in step 3) x @ZIF-8 composite structure powder is heated and carbonized in an inert gas, and Ni3ZnC is collected. 0.7 @NiZn catalyst.

3. A Ni3ZnC according to claim 2 0.7 @The preparation method of NiZn catalyst is characterized by In step 1), the mass volume ratio of nickel nitrate to ethylene glycol is 1 g: (10-30) mL; the hydrothermal reaction in step 1) is carried out at 100° C. to 180° C. for 2 to 6 hours; and the stirring time in step 2) is 0.5 to 2 hours.

4. A Ni3ZnC according to claim 2 0.7 @The preparation method of NiZn catalyst is characterized by The concentration of zinc nitrate in the methanol solution containing zinc nitrate in step 2) is 0.05 mol / L to 0.1 mol / L; the volume ratio of the colloid to the methanol solution containing zinc nitrate in step 2) is 1:(10-20).

5. A Ni3ZnC according to claim 2 0.7 @The preparation method of NiZn catalyst is characterized by The concentration of 2-methylimidazole in the methanol solution containing 2-methylimidazole in step 3) is 0.1 mol / L to 0.5 mol / L; the volume ratio of the mixed liquid to the methanol solution containing 2-methylimidazole in step 3) is 1:(0.5-2).

6. Ni3ZnC according to claim 2 0.7 @The preparation method of NiZn catalyst is characterized by The stirring time in step 3) is 1 to 3 hours; the standing time at room temperature in step 3) is 1 to 6 hours.

7. Ni3ZnC according to claim 2 0.7 @The preparation method of NiZn catalyst is characterized by In step 4), NiO x The ZIF-8 composite structure powder is first heated to 300°C in an inert gas and maintained for 1 hour, and then heated to 750°C to 850°C for heating and carbonization. The heating time is 1 to 4 hours.

8. A method using Ni3ZnC 0.7 A method for preparing an electrocatalytic carbon dioxide reduction electrode using a NiZn catalyst is characterized by: include: Step (1), Ni3ZnC 0.7 @NiZn catalyst, dispersion liquid and binder are mixed in a certain ratio and ultrasonically dispersed to form a solution; Step (2): evenly apply the solution formed in step (1) on the hydrophobic carbon paper and air dry it to obtain the diatomic catalyst Ni3ZnC 0.7 @NiZn electrode.

9. A method according to claim 8 using Ni3ZnC 0.7 A method for preparing an electrocatalytic carbon dioxide reduction electrode using a NiZn catalyst is characterized by: The dispersion liquid is any one of deionized water, anhydrous ethanol, and isopropyl alcohol, or a combination of several thereof; the binder is any one of polyacrylic acid, perfluorinated resin, and fluorinated ethylene propylene copolymer, or a combination of several thereof.

10. A method according to claim 8 using Ni3ZnC 0.7 A method for preparing an electrocatalytic carbon dioxide reduction electrode using a NiZn catalyst is characterized by: The Ni3ZnC 0.7 @The mass volume ratio of NiZn catalyst, dispersion liquid and binder is 1 mg: (50-100) ml: (1-10) ml.